Eyewitness Identification Jury Instructions: Do They Enhance Evidence Evaluation? - Berman, Marlee Kind (2015)
Mistaken eyewitness identifications are a leading cause of wrongful convictions. Even with procedural safeguards (e.g., cross-examination) in place, jurors still have difficulty evaluating the reliability of eyewitness identifications. The purpose of the present line of research is to examine whether the issue-specific judicial instructions, set forth by the New Jersey Supreme Court (New Jersey v. Henderson, 2011), effectively sensitize jurors to eyewitness identification accuracy. Results of the first study indicate that the current Henderson instructions delivered on issues specific to a case are not as effective as intended. Results of the second study indicate a sensitivity effect, such that mock jurors were most sensitive to the quality of the eyewitness identification when they received judicial instruction on all eyewitness variables and evaluated the evidence prior to rendering a verdict. Implications of the research as well as ideas for future research are discussed